The Impact of Emotional Intelligence on the Academic Performance of Students with Intellectual Disabilities in Inclusive Education - Vovchenko, Olha; Leonova, Inna; Soroka, Iryna; Klymenko, Iryna; Tsekhmister, Yaroslav (Journal of Intellectual Disability - Diagnosis and Treatment, 2022)
Background: The development of inclusive education involves the increasing participation of children and adolescents with intellectual disabilities in the general education process, which can be accompanied by several stressful and psychotraumatic situations that negatively affect the academic success of such adolescents. Objective: This study aimed to empirically test the probability that the emotional intelligence level of adolescents with intellectual disabilities impacts their academic performance. Methods: The study was conducted as a socio-psychological experiment involving experimental and control groups through pre-test and post-test measurements of the emotional intelligence level of adolescents with intellectual disabilities and their academic performance. The study involved students at comprehensive secondary schools aged 12-14 who studied in inclusive classes. Results: The Emotional Intelligence Development Programme also aimed to further the inclusion of adolescents in their school lives. The Programme involved a series of classes with a predominance of visual material adapted to the needs of adolescents with intellectual disabilities. The research was motivated by the improvement of inclusive education in Ukraine, which is at the stage of its formation. The Programme is based on applied developments of practical psychologists with the author's extensions. The study was carried out through the EmIn Test adapted by Lyusin to diagnose the level of emotional intelligence. Observations, one-way analysis of variance (ANOVA), Pearson correlation coefficient, and comparison of means through student's t-test were used to analyze the data obtained. The Programme resulted in increased parameters for the emotional intelligence level in the experimental group compared to the control group and improved academic performance in Mathematics and Biology. The results obtained empirically confirmed the positive impact of emotional intelligence on the academic performance of children with intellectual disabilities. Conclusion: The primary value of the study was the integration of the author's approaches in the development of emotional intelligence of adolescents with intellectual disabilities. The practical result of the research is the methodological systematization of the experiment results with the aim of further implementation in the general educational process. Further research suggests monitoring the long-term effects of therapeutic intervention programs in working with adolescents with intellectual disabilities.